Efficacy and safety of triple combination therapy with artesunate-amodiaquine-methylene blue for falciparum malaria in children: a randomized controlled trial in Burkina Faso - Coulibaly, Boubacar; Pritsch, Michael; Bountogo, Mamadou; Meissner, Peter; Nebié, Eric; Klose, Christina; Kieser, Meinhard; Berens-Riha, Nicole; Wieser, Andreas; Sirima, Sodiomon; Breitkreutz, Jörg; Schirmer, Rolf Heiner; et al. (The journal of infectious diseases, 2015)
Background. Methylene blue (MB) has been shown to be safe and effective against falciparum malaria in Africa and to have pronounced gametocytocidal properties.Methods. Three days of treatment with artesunate (AS)-amodiaquine (AQ) combined with MB was compared with AS-AQ treatment in a randomized controlled phase IIb study; the study included 221 children aged 6-59 months with uncomplicated falciparum malaria in Burkina Faso. The primary end point was gametocyte prevalence during follow-up, as determined by microscopy and real-time quantitative nucleic acid sequence-based amplification (QT-NASBA).Results. The gametocyte prevalence of Plasmodium falciparum at baseline was 3.6% (microscopy) and 97% (QT-NASBA). It was significantly lower in the AS-AQ-MB than in the AS-AQ group on day 7 of follow-up (microscopy, 1.2% vs 8.9% [P < .05]; QT-NASBA, 36.7% vs 63.3% [P < .001]). Hemoglobin values were significantly lower in the AS-AQ-MB group than in the AS-AQ group at days 2 and 7 of follow-up. Vomiting of the study medication occurred significantly more frequently in the AS-AQ-MB group.Conclusions. The combination of MB with an artemisinin-based combination therapy has been confirmed to be effective against the gametocytes of P. falciparum. MB-based combinations need to be compared with primaquine-based combinations, preferably using MB in an improved pediatric formulation.Clinical Trials Registration. NCT01407887.
Gesehen am 10.12.2020
Published:28 September 2014